A cost‐effectiveness analysis of two different repositioning strategies for the prevention of pressure ulcers. (27th August 2015) - Marsden, Grace; Jones, Katie; Neilson, Julie; Avital, Liz; Collier, Mark; Stansby, Gerard
Abstract: Aims: To assess the cost effectiveness of two repositioning strategies and inform the 2014 National Institute for Health and Care Excellence clinical guideline recommendations on pressure ulcer prevention. Background: Pressure ulcers are distressing events, caused when skin and underlying tissues are placed under pressure sufficient to impair blood supply. They can have a substantial impact on quality of life and have significant resource implications. Repositioning is a key prevention strategy, but can be resource intensive, leading to variation in practice. This economic analysis was conducted to identify the most cost‐effective repositioning strategy for the prevention of pressure ulcers. Design: The economic analysis took the form of a cost‐utility model. Methods: The clinical inputs to the model were taken from a systematic review of clinical data. The population in the model was older people in a nursing home. The economic model was developed with members of the guideline development group and included costs borne by the UK National Health Service. Outcomes were expressed as costs and quality adjusted life years. Conclusion: Despite being marginally more clinically effective, alternating 2 and 4 hourly repositioning is not a cost‐effective use of UK National Health Service resources (compared with 4 hourly repositioning) for this high risk group of patients at a cost‐effectiveness threshold of £20, 000 per quality adjusted life years. These results were used to inform the clinical guideline recommendations for those who are at high risk of developing pressure ulcers.